2009
DOI: 10.1007/s11259-009-9236-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and urine profile of tramadol and its major metabolites following oral immediate release capsules administration in dogs

Abstract: The aim of the present paper was to test the oral administration of oral immediate release capsules of tramadol in dogs, to asses both its pharmacokinetic properties and its urine profile. After capsules administration of tramadol (4 mg/kg), involving eight male Beagle dogs, the concentration of tramadol and its main metabolites, M1, M2 and M5, were determined in plasma and urine using an HPLC method. The plasma concentrations of tramadol and metabolites were fitted on the basis of mono- and non-compartmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 24 publications
4
30
0
2
Order By: Relevance
“…Several studies have examined the pharmacokinetics of oral tramadol in dogs, but these studies were limited to 2 studies in Beagles, 7,32 and one with Greyhounds. 8 These studies measured different metabolites with different methods, so comparison is somewhat difficult, and all three studies revealed a large variation between subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the pharmacokinetics of oral tramadol in dogs, but these studies were limited to 2 studies in Beagles, 7,32 and one with Greyhounds. 8 These studies measured different metabolites with different methods, so comparison is somewhat difficult, and all three studies revealed a large variation between subjects.…”
Section: Discussionmentioning
confidence: 99%
“…6 Early research indicated when given orally to dogs, at doses of 4 mg/kg, tramadol achieves therapeutic plasma levels within 5 minutes and persists in plasma at measurable concentrations for between 5 – 10 hours. 7 More recent research showed that at a dose of 10mg/kg given orally to dogs, many of the metabolites thought to be important for opioid-mediated analgesia achieved very low plasma concentrations, suggesting that the reported analgesic effects may be independent of opioid activity. 8 Despite tramadol’s interesting mechanisms, little is published regarding its analgesic efficacy in dogs when given orally for either post-surgical pain or chronic pain.…”
mentioning
confidence: 99%
“…While pharmacokinetic studies have documented variability in tramadol metabolism between dogs, low plasma concentrations of M1 have been detected in most studies (KuKanich & Papich , ; Giorgi et al. ,b,c,d, ). In addition, M1 has a 400‐fold increased affinity for the μ receptor compared to tramadol in humans (Gillen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been used for some time now, our understanding and ability to predict the time course of its pharmacological effects in animals are still hampered by the presence of active metabolites and the coexistence of opioid and non-opioid mechanisms. Recently, T has been reported to be metabolized faster to inactive metabolites N-desmethyl tramadol (M2) and O,N-didesmethyl tramadol (M5), in goats (Sousa et al, 2008), dogs (McMillan et al, 2008;Giorgi et al, 2009a;2009b;2009c;2009d;2010a;Kukanich and Papich, 2011), horses (Giorgi et al, 2007;Shilo et al, 2008;Cox et al, 2010;Giorgi et al, 2010b), llamas , alpacas (Giorgi et al, 2010c), peafowl (Black et al, 2010), hawks than in cats (Pypendop and Ilkiw, 2008). The use of T has also been suggested for zoo animals .…”
Section: Tramadolmentioning
confidence: 99%
“…It is possible therefore that this drug may not provide as effective and safe treatment for pain as in humans (Giorgi et al, 2007;2009a;2009b;2009c;2009d;2010a;2010c;Sousa et al, 2008;Kukanich and Papich, 2011). No stereoselective pharmacokinetic studies on T and its metabolite have been reported in animals to date.…”
Section: Tramadolmentioning
confidence: 99%